Academic integrity among nursing students: A survey of knowledge and behavior - Nortes, Isabelle (Nursing ethics, 2024)
BackgroundMinimal research has been done to determine how well European nursing students understand the core principles of academic integrity and how often they deviate from good academic practice.AimThe aim of this study was to find out what educational needs nursing students have in terms of academic integrity.Research designA quantitative cross-sectional study in the form of a survey of nursing students was conducted via questionnaire in the fall of 2020.ParticipantsThe sample was composed of 79 students in the BScN and MScN programs at Zürich University of Applied Sciences.Ethical considerationsAn application for a non-competence clearance was approved by the Ethics Committee in Zurich (BASEC No. Req-2020-00868). The survey was anonymous, and informed consent was obtained prior to participation.ResultsThe participants had a high level of confidence in their own knowledge but were in many cases unable to correctly identify clear-cut examples of misconduct and to differentiate them from questionable practices. About 13% of the participants admitted that during their university education they had copied shorter passages from other sources into their own text without marking them as quotes.ConclusionsThe study documents extensive knowledge gaps among nursing students regarding both academic misconduct and questionable practices and indicates a need for improved academic integrity training.